8,9-Methylenedioxybenzo[i]phenanthridines_ Topoisomerase I-Targeting activity and cytotoxicity - Li, D.; Zhao, B.; Sim, S.P; Li, T.K; Liu, A.; Liu, L.F.; LaVoie, E.J. (Elsevier Ltd, 2003)
Substituted benzo[i]phenanthridines that have incorporated within their structure an 8,9-methylenedioxy group can exhibit topoisomerase I-targeting activity. Structure–activity studies were performed to examine the influence of saturation at the 11,12-positions of several substituted 8,9-methylenedioxybenzo[i]phenanthridines. The activities of these dihydro analogues were compared to those of their unsaturated analogues. In addition, the influence of varying substituents at the 2- and 3-positions within the A-ring of these 8,9-methylenedioxybenzo[i]phenanthridines on their relative potency as topoisomerase I-targeting agents and cell proliferation as determined using the MTT assay was investigated. 2,3-Dimethoxy-8,9 Methylenedioxybenzo[i]phenanthridine and its 11,12-dihydro derivative were among the more potent analogues evaluated with regard to topoisomerase I-targeting activity and cytotoxicity.